2023
DOI: 10.21273/horttech05110-22
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Bioinoculants Increase Root Length Colonization and Improve Petiole Nutrient Concentration of Field-grown Grapevines

Abstract: Agricultural bioinoculants containing arbuscular mycorrhizal fungi represent a potential opportunity to reduce the dependence of grapevines (Vitis) on agrochemicals. This field study assessed the ability of four commercial bioinoculants to colonize grapevine roots and their effects on petiole nutrient concentration, berry composition, and root morphology of ‘Pinot noir’ (Vitis vinifera) grafted onto rootstock ‘Couderc 3309’ (Vitis riparia × Vitis rupestris) and ‘Riesling’ (V. vinifera) grafted onto ‘Couderc 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Boosting root colonization in that trial is not surprising, given such a low level of natural root colonization, although why it was so low to begin with is not clear. Inoculation with commercial AMF products also enhanced root colonization from ~60% in uninoculated controls to 70% RL in 10-year-old Pinot noir vines on 3309C rootstock, and from ~50% in the controls to 60% of RL in 20-year-old Riesling vines on 3309C or SO4 rootstocks in New York vineyards (Berdeja et al 2023). Others have reported increased AMF colonization after inoculating vines with commercial products in young vineyards, where a greater response might be expected due to loss of AMF propagules after tilling and preparing the soil, and a potential lack of AMF in planting stock (Mikiciuk et al 2019, Torres et al 2021).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Boosting root colonization in that trial is not surprising, given such a low level of natural root colonization, although why it was so low to begin with is not clear. Inoculation with commercial AMF products also enhanced root colonization from ~60% in uninoculated controls to 70% RL in 10-year-old Pinot noir vines on 3309C rootstock, and from ~50% in the controls to 60% of RL in 20-year-old Riesling vines on 3309C or SO4 rootstocks in New York vineyards (Berdeja et al 2023). Others have reported increased AMF colonization after inoculating vines with commercial products in young vineyards, where a greater response might be expected due to loss of AMF propagules after tilling and preparing the soil, and a potential lack of AMF in planting stock (Mikiciuk et al 2019, Torres et al 2021).…”
Section: Discussionmentioning
confidence: 88%
“…While our results showed that grapevine roots become well-colonized with fewer AMF propagules and that colonization of AMF of roots in the region's vineyards was high even in young vineyards, we do not imply that inoculating vines with AMF will not further enhance root colonization and potentially benefit vine health. Adding AMF inoculum even to older vines has increased root colonization in some cases (Nicolás et al 2015, Berdeja et al 2023. Inoculating 10-year-old V. vinifera Crimson Seedless vines in a vineyard in Spain with a lab-produced AMF inoculum increased root colonization to 60% of RL, rather than only 10 to 20% RL colonized in the existing, uninoculated, control vines (Nicolás et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For all the above‐mentioned reasons, AMF have been used to produce PP – as single species or as consortia with other AMF, ectomycorrhizal fungi, or PGP bacteria – and applied for several decades, mainly to improve horticulture and grain crop productivity (Basiru et al., 2021 ; Berdeja et al., 2023 ) while reducing environmental costs (Berruti et al., 2016 ).…”
Section: Fungi As Plant Growth‐promoting Microorganismsmentioning
confidence: 99%